Report of an Outbreak of Peste Des Petits Ruminants in Iran, Clinical, Epidemiological and Pathological Study - Mohebbi, Mohammad Reza; Heydary-Sureshjani, Masoumeh; Marjanmehr, Seyed Hossein; Khaligh, Sahar Ghaffari (International Journal of Veterinary Sciences Research, 2018)
Peste des petits ruminants (PPR) is an acute to sub-acute highly contagious and frequently fatal viral disease of goats and sheep and wild small ruminants caused by a virus in the genus morbilivirus, family paramyxoviridae. The flock of sheep including 800 fattening sheep were affected and the presence of PPR virus was assayed with RT-PCR test. The only significant change in the CBC was leucopenia. There were typical lesions on dental pad, hard palate, gingiva and tongue. The Morbidity and case fatality rates were estimated 50 and 60 percent, respectively. All deaths were happen in lambs and young sheep. Results of the histopathologcal findings indicated that the lesions were mainly located on the respiratory system, upper digestive system, kidney and lymphoid organs. Infiltration of mononuclear and inflammatory cells in lamina propria were seen in mouth, soft palate, intestines, lung, and tonsil. Secondary infection as result of immunosuppression activity of the PPR virus was happened and resulted in high mortality and case fatality. The present paper reports an outbreak of PPR in a sheep flock in Karaj, Alborz province in Iran, including pathological, and clinical observation and also serological detection.